Pervasive information architecture : designing cross-channel user experiences - Resmini, Andrea; Rosati, Luca , 1971- (Elsevier, 2011)
As physical and digital interactions intertwine, new challenges for digital product designers and developers, as well as, industrial designers and architects are materializing. While well versed in designing navigation, organization, and labelling of websites and software, professionals are faced the crucial challenge of how to apply these techniques to information systems that cross communication channels that link the digital world to the physical world. Pervasive Information Architecture provides examples showing why and how one would: Model and shape information to adapt itself to users' needs, goals, and seeking strategies Reduce disorientation and increase legibility and way-finding in digital and physical spaces Alleviate the frustration associated with choosing from an ever-growing set of information, services, and goods Suggest relevant connections between pieces of information, services and goods to help users achieve their goals. *Master agile information structures while meeting the unique user needs on such devices as smart phones, GPS systems, and tablets *Find out the 'why' and 'how' of pervasive information architecture (IA) through detailed examples and real-world stories *Learn about trade-offs that can be made and techniques for even the most unique design challenges